PEMBIASAAN PERILAKU RELIGIUS PADA SISWA MI UNGGULAN NURUL ISLAM WONOGIRI (PERSPEKTIF PENDEKATAN BEHAVIORISTIK) - Novitasari, Giyarmi (Jurnal Jaringan Penelitian Pengembangan Penerapan Inovasi Pendidikan (Jarlitbang), 2025)
The purpose of this research is to find out the role of the teacher in carrying out religious habituation through a behavioristic approach.The type of research used is field research, because the data information needed is dug up and collected from the field. This research method is descriptive qualitative in nature, meaning that research is about descriptive research. Research data collection techniques through observation, interviews, and documentation.The results of his research are: 1) the habituation of religious behavior is continuous repetition over a long period of time with the aim of increasing sincerity in perfect religiosity in a good and right way. The religious activities include: a) the ritual dimension (shari'ah); b) ideological dimension (aqidah); c) intellectual dimension (knowledge); d) the dimension of experience or appreciation (experiential); e) the consequential dimension (practice). Linkages to the five religious dimensions, MI Nurul Islam teachers familiarize students with activities gradually; 2) As for the impact of habituation of religious behavior on MI Nurul Islam Wonogiri students from the stimulus that has been carried out by both parents and teachers, the impact on increasing the response is very good. This can be seen from the student's response to being accustomed to applying the five religious dimensions. 3) When students are given a stimulus by giving a good example in the form of thoughts, actions and words, providing guidance, direction, approaching and working with the student's guardians where it is consistently accustomed to every dimension of religious habituation, the student's response becomes accustomed to and loves the five religious dimension to be applied in everyday life as a form of human being who believes and fears God.